UNSUR RELIK BAHASA JAWA KUNA PADA BAHASA JAWA DIALEK BANYUMAS DAN BAHASA JAWA STANDAR - , ERWITA NURDIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Javanese division of history periods is grouped into Old Javanese, Middle Javanese and New Javanese. The division of history periods of Javanese usage is based on the consideration of the empire power, linguistic features and time of usage. The old Javanese is as one of Nusantara language in the Austronesia and it is supposed to inherit linguistic elements in New Javanese. The focus of this research is Javanese, Banyumas dialect and Javanese, standard dialect by considering standard dialect is in culture center, while Banyumas dialect is far from culture center. This research examines the elements of Old Javanese inheritance toward Javanese Banyumas dialect and Javanese, standard dialect by using field research method and literature method. In determining Old Javanese Vocabularies refers to Zoetmulder work in title Old Javanese-English Dictionary (2006), Kamus Jawa Kuno (Kawi-Indonesia) by L.Mardiwarsito (1978) and Kamus Kawi (Djawa Kuno)- Indonesia third edition by Wojowasito based on Soewito Santoso. Qualitative evidences show that there is innovation and retention in phonological element and lexicon obtained through phonological reconstruction, that is the invention of sound change principle sporadically, such as ellipsis, lenition, ephenthesis, sinkope, apokope, aphaeresis, protesis, fortisi, monoftongisasi and metathesis in both of vocal and consonant phoneme. Lexicon construction is meaning difference in lexeme and word formation in Old Javanese toward Javanese, Banyumas dialect and Javanese, standard dialect.